Analisis Penerapan Manajemen Sumber Daya Manusia Islami Pada UMKM di Kota Langsa - Mastura (Fakultas Ekonomi dan Bisnis Islam, 2024)
One of the excellent Small Micro and Medium Enterprises using the sharia system in Langsa City is a business engaged in the service sector, however, it is unfortunate that Small Micro and Medium Enterprises in Langsa City have not fully paid attention to the application of Islamic human resource management in running their business. This study aims to know how the understanding of the owners of Langsa's MSMEs about Islamic resource management, how to apply Islamic resource management in the recruitment, selection, training and development process, performance appraisal and compensation for MSMEs in Langsa City and what are the obstacles in the application of Islamic resource management to MSMEs in Langsa City. This research is a qualitative research whose research subjects are business actors engaged in services using sharia principles in Langsa City. The results showed that based on the results of the study, it was found that the owners of MSMEs basically already understand several things related to Islamic human resource management even though some of them do not know that what they are implementing is part of Islamic resource management. In relation to its implementation, these five MSMEs have implemented Islamic human resource management which consists of aspects: recruitment, selection, work contracts and compensation, while they do not fully implement training and development, while the obstacles faced by the application of Islamic values according to the MSME owners are the first, not all employees have the same understanding and second is to equalize goals (goals).